2022
DOI: 10.3390/jcm11174946
|View full text |Cite
|
Sign up to set email alerts
|

Migraine Prevention through Ketogenic Diet: More than Body Mass Composition Changes

Abstract: The ketogenic diet (KD) is gaining attention as a preventive treatment for migraine, which is sustained by many pre-clinical and clinical data. KD is also used for weight loss, and there is a relation between migraine and weight excess, but it is speculated that KD efficacy on migraine may go beyond this effect. We conducted a retrospective observational study on 23 migraine patients who received a KD and were evaluated at the baseline and then after 3 months both from a neurological and a nutritional point of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…Consequently, the studies suggest that there is potential for an increase in the strength of the intervention groups' immune systems due to the intake of the ketogenic diet, unlike the control group. Finally, the average p-value of the research articles was p = 0.09, with 15 out of the 20 studies being considered as statistically significant in that that they had p values less than 0.05 at 95% CI [1], [2], [3], [4], [10], [11], [12], [13], [14], [15], [16], [19], [20], [21], [22]. For that reason, more than half of the research studies used in the current meta-analysis failed to reject their null hypotheses that the ketogenic diet had a positive effect on the human immune system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the studies suggest that there is potential for an increase in the strength of the intervention groups' immune systems due to the intake of the ketogenic diet, unlike the control group. Finally, the average p-value of the research articles was p = 0.09, with 15 out of the 20 studies being considered as statistically significant in that that they had p values less than 0.05 at 95% CI [1], [2], [3], [4], [10], [11], [12], [13], [14], [15], [16], [19], [20], [21], [22]. For that reason, more than half of the research studies used in the current meta-analysis failed to reject their null hypotheses that the ketogenic diet had a positive effect on the human immune system.…”
Section: Resultsmentioning
confidence: 99%
“…That is because they mainly comprise a combination of foods such as vitamins and proteins, which are essential in the production of white blood cells, which boosts the immune system [12], [13], [14], [15], [16]. Since many foods with unsaturated fats, such as avocado, meat, and cheese, do not contribute positively towards increased white blood cells production, ketogenic foods were considered to be less effective in improving the human immune system by the researchers of the analyzed studies [14], [15], [16], [19], [20], [21], [22]. For that reason, the researchers suggested that there is a need to supplement ketogenic foods with foods from other diets to improve their effectiveness in decreasing the risk of various chronic diseases and enhancing the strength of the immune system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, body mass, fatty tissue mass and, thus, BMI values were also reduced in these patients. The favourable influence goes beyond the effect of body weight loss, and the authors concluded that other mechanisms must underlie the therapeutic activity [ 218 ]. The aim of another study in 2022 was an assessment of the effect of the ketogenic diet on treatment-refractory migraine in 22 patients (in the first study) and 31 subjects (in the second study).…”
Section: Ketogenic Diet In the Therapy Of Migrainementioning
confidence: 99%
“…In the short term, it has been reported as being associated with a reduction in headache frequency and painkillers, coupled with weight loss and a reduction in fat mass. The putative mechanism has not been elucidated; however, if a ketogenic diet is indicated in the patient for other health reasons, it could add more data about the effects of dietary conduits on headaches [ 11 ].…”
mentioning
confidence: 99%